Increasing the Production of Valuable Phytopharmaceutical Compounds by Chromosome Manipulation: Perspectives and Techniques of Induction and Selection of Polyploid Plants - E Ghotbi Ravandi; E Dehghan; AR Estaji; H Naghdi Badi (Institue of Medicinal Plants, ACECR, 2014)
Polyploidy is one of the widespread phenomena in plant kingdom, which has a vital role in evolution and speciation of plants and is usually accompanied by significant changes in morphology, cell and organ size, expression patterns of genes, respiration and phtotosynthesis, regeneration ability, fertility, biochemistry and metabolom of plants. Therefore polyploidy, especially tetraploidy, has been widely applied in modification of various characteristics of plants. The diversity of traits resulted by the induction of polyploidy, depends on the genotype and species and therefore is not always useful. Though tetraploidy usually results in fewer seeds and decrease of fertility but in cases where the increase in biomass or concentration of medicinal compounds is of importance, it can be efficiently applied for breeding of medicinal plants. Autotetraploidy doubles the gene dosage and allotetraploidy collects the useful allels of a biosynthetis pathway in a resulted hybrid and therefore may improve the production of secondary metabolites. According to the importance of herbal medicine and increasing demand for medicinally important secondary metabolites in our country, we describe the effects of polyploidy on various characteristics of medicinal plants and the methods of induction and selection of polyploid plants in this paper.